Mycotoxins presence in woodworking environments from Portugal - Dias, Marta (2024)
Woodworkers may be exposed to a variety of chemicals and natural toxins that might be harmful to their health, including wood preservation products as well as metabolites produced by the microorganisms that grow on wood, such as mycotoxins. This study intends to characterize the mycotoxin's presence in two woodworking environments in Portugal.